ARTHROSCOPY OF THE SCAPULOTHORACIC JOINT: CASE REPORTS - Andreoli, Carlos Vicente (Elsevier, 2015)
Scapulothoracic arthroscopy is a procedure presenting restricted indications, for resecting free bodies, benign tumors, bursitis, and snaping scapula. The authors report four cases of scapulothoracic joint arthroscopy; in the first case, only a benign tumor (osteochondroma) could be visualized; in the second case, arthroscopic resection of an osteochondroma was found; in the third case, arthroscopic bursectomy due to scapulothoracic bursitis, and; in the fourth case, bursectomy and partial superomedial arthroscopic scapulectomy due to snaping scapula.